2021
DOI: 10.1002/jlb.4a0220-114rr
|View full text |Cite
|
Sign up to set email alerts
|

Selective killing of human M1 macrophages by Smac mimetics alone and M2 macrophages by Smac mimetics and caspase inhibition

Abstract: The inflammatory and anti‐inflammatory Mϕs have been implicated in many diseases including rheumatoid arthritis, multiple sclerosis, and leprosy. Recent studies suggest targeting Mϕ function and activation may represent a potential target to treat these diseases. Herein, we investigated the effect of second mitochondria‐derived activator of caspases (SMAC) mimetics (SMs), the inhibitors of apoptosis (IAPs) proteins, on the killing of human pro‐ and anti‐inflammatory Mϕ subsets. We have shown previously that hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 78 publications
2
13
0
Order By: Relevance
“…HIV infection results in dysregulation of cytokine profile in-vivo and in-vitro 62 and can possibly affect the polarization state of macrophages . Since IFN-γ-generated M1 macrophages are susceptible to SM-mediated cell death 49 , HIV-1 infection may polarize macrophages into M1 phenotype and make them susceptible to SM-induced apoptosis. Since in vitro-infected and ex vivo - derived macrophages exposed to SM were not polarized into M1 phenotype suggested that SM-mediated killing of HIV-infected macrophages was not due to M1 polarization.…”
Section: Discussionmentioning
confidence: 99%
“…HIV infection results in dysregulation of cytokine profile in-vivo and in-vitro 62 and can possibly affect the polarization state of macrophages . Since IFN-γ-generated M1 macrophages are susceptible to SM-mediated cell death 49 , HIV-1 infection may polarize macrophages into M1 phenotype and make them susceptible to SM-induced apoptosis. Since in vitro-infected and ex vivo - derived macrophages exposed to SM were not polarized into M1 phenotype suggested that SM-mediated killing of HIV-infected macrophages was not due to M1 polarization.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the infiltration of effector T cells within tumors treated with tSMAC show low expression of PD-1 ( 12 ). It was also shown that SMAC mimetics, which competitively inhibit SMAC-cIAP-1/2 interaction and thus repress anti-apoptotic functions of IAP proteins, elicit proinflammatory cell death in cancer cells that engages an adaptive antitumor immune response ( 104 ). These finding support our results proposing an additional function for SMAC related to anti-tumor immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that second mitochondriaderived activator of caspases (SMAC) mimetics (SMs) can inhibit the anti-apoptotic effect of Smac, which is a member of the IAP family protein, by competing with CIAP1/2 protein to induce the activation of caspase-3, caspase-7, caspase-8, caspase-9, and Fas; thereby facilitating the release of TNF-a; and in vitro activation of RIPK1, RIPK3, and MLKL in pro-inflammatory M1 macrophages to activate apoptosis and necroptosis. Blockade of the IAP and caspase pathways, facilitates M2c phenotype induction by SMs, resulting in necroptosis of M0 macrophages (177). Compared with etanercept, a TNF-a inhibitor, geldanamycin inhibits the RIPK1 and NF-KB activity while augmenting the activation of caspase-8 to promote MH7A cell apoptosis, and inhibit TNF-a-induced necroptosis.…”
Section: Necroptosis In the Pathophysiology Of Rheumatoid Arthritismentioning
confidence: 99%